OVERLAP TYPES IN GOLDEN GLOBE AWARD INTERVIEW BY THE HOLLYWOOD REPORTER - Nia Denisa; Toneng Listiani; Hasbi Assiddiqi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
The aim of this research is to categorize what types of overlap are constructed in Golden Globe Award Interview 2020 with Nicholas Braun by The Hollywood Reporter. In an interview, it is one of turn taking violations which still becomes a rife phenomenon where many speakers aren’t aware yet about it. The approach used in this research is descriptive qualitative by documentation technique. The main theory of overlap types is based on Schegloff (2000) and French & Local (1983). There are 13 data found which contain 11 non-competitive: 1 terminal overlap, 5 continuers, 4 conditional access to the turn, 1 choral and 2 competitive: 2 high pitch and increased loudness. So, it can be concluded that the most dominant of overlap type is continuers that categorized as unproblematic for the speakers and conversation structure. Because the next speakers used it to respect the current speakers. Therefore, this result is expected as one of overlap examples which can be applied.